2014
DOI: 10.1007/s12603-014-0496-2
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of energy-dense, small volume oral nutritional supplements in the daily clinical practice on a geriatric ward — An observational study

Abstract: This study shows that compliance to ED-ONS is significantly better than to S-ONS in daily clinical practice. Although small, the difference in compliance seems to increase over time, suggesting clinical relevance with longer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…50 A strength of the present study was the high compliance to the ONS and the adherence to the psychomotor rehabilitation program by the patients, family, caregivers, and the nursing staff. As expected and according to the previously described by Lombard et al, 51 a small volume high-protein energy-dense liquid ONS (125 mL) has shown to improve compliance in clinical trials, optimizing the clinical effectiveness of oral nutritional supplements. A limitation of our study that should be acknowledge is the lack of a random sample allocation of the NSPRG participants.…”
supporting
confidence: 77%
“…50 A strength of the present study was the high compliance to the ONS and the adherence to the psychomotor rehabilitation program by the patients, family, caregivers, and the nursing staff. As expected and according to the previously described by Lombard et al, 51 a small volume high-protein energy-dense liquid ONS (125 mL) has shown to improve compliance in clinical trials, optimizing the clinical effectiveness of oral nutritional supplements. A limitation of our study that should be acknowledge is the lack of a random sample allocation of the NSPRG participants.…”
supporting
confidence: 77%
“…Enteral nutrition is an effective strategy for treating and avoiding malnutrition and is given as an oral nutritional supplement (ONS) when the patient is able to take it orally. A positive correlation has been reported between the compliance and energy density of ONS [12][13].…”
Section: Discussionmentioning
confidence: 78%
“…For patients who are unable to take enough nutritional supplements orally, they are fed using an enteral tube into the stomach or small intestine [9]. The energy density of commercialized formulations is approximately in the range of 0.5-2.4 kcal/mL [9,12]. Enteral nutrition is an effective strategy for treating and avoiding malnutrition and is given as an oral nutritional supplement (ONS) when the patient is able to take it orally.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the mixed-effects model was employed to account for within-patient correlation introduced by repeated measurements. This model is often used to correct for individual patient differences in repeated measures [23,24]. Fig 3 shows that the fitting of the model to data is fairly good.…”
Section: Plos Onementioning
confidence: 94%